(untitled) (Experimental biology, 2015)
The genetics of specific traits of wheat is analysed. Taxonomic traits by K.Linneey are based on the minor genes and аre controlled by very simple gene (1-3 and polymeric) relation. These simple gene relations can’t be sufficient criterion for definition of the specific status. From a point allopolyploidy evolution and alteration of fragility of an ear of wild species are the basic systems of formation of species. Wild tetraploid wheat – Emmer has arisen by this way. So, together with a result of long-term researches of interspecific hybrids of wheat, it is offered to include in species of Triticum only seven species: T.boeticum, T.urartu T.araraticum, T.dicoccoides, T.timopheevi, T.dicoccum, T.spelta. All other species concern to natural cultural ecology-geographical categories - species and subspecies of wheat.